The Emergence of Female Identity in Sefi Atta’s Everything Good Will Come - Anato, Sylvain; Aïnamon, Augustin; Gbaguidi, Célestin (Advances in Social Sciences Research Journal, 2023)
Everything Good Will Come (2006) is the debut novel by the Yoruba author Sefi Atta. She investigates the different transformation that occur in the life of Enitan, the female protagonist of the novel, while she makes her tedious journey from the beginning of adolescence to adulthood. For a long time, women have almost played secondary roles in the Nigerian novel in the struggle to address socio-political and economic challenges. However, since the beginning of the 2000s, Nigerian fiction has presented women in leadership roles in their societies. In fact, a new generation of authors has emerged. Atta has become a famous and internationally acclaimed writer of this series in her quest to demonstrate how the identity of a woman can originate from various hostile factors that affect her environment. She suggests that this can only happen if and only women are self-affirming, become fully aware of unlocking their tremendous inner potential which is essential to reverse the trend of a fiction plot dominated by men. Indeed, Everything Good Will Come is a counter-speech to the almost pitiful image of the woman in works mainly masculine.